High-throughput prediction and characterization of antimicrobial peptides from multi-omics datasets of Chinese tubular cone snail (Conus betulinus) - Li, Ruihan; Huang, Yu; Peng, Chao; Gao, Zijian; Liu, Jie; Yin, Xiaoting; Gao, Bingmiao; Ovchinnikova, Tatiana V.; Qiu, Limei; Bian, Chao; Shi, Qiong (Frontiers in Marine Science, 2022)
Individual cone snail (Conus sp.) contains thousands of bioactive peptides, but there are limited studies on its antimicrobial peptides (AMPs). Here, we investigated AMPs along with AMP-derived genes in the representative Chinese tubular cone snail (C. betulinus) by integration of our previously published multi-omics (genomics, transcriptomics, and peptidomics) data. We identified a total of 466 putative AMP-derived genes from the genome, and most of them were annotated as histones. While at the mRNA level, only 77 AMP-derived genes were confirmed with transcriptomic evidence, among them Ubiquicidin, cgUbiquitin, Ap, and VK10 were the most abundant transcripts in the venom gland. In addition, 30 AMPs were further validated by peptidomics data. After in silico analysis including 3D modeling, 11 putative AMPs were chemically synthesized for an in vitro assessment, and eight peptides were proved with good antifungal activity. In summary, this work systematically characterized the AMP repertoire in C. betulinus. This valuable genetic resource provides a solid foundation for in-depth therapeutic applications and drug development.